Social Exchange in Community-Based Peer-2-Peer Ridesharing: A Qualitative Approach - Santa, Mijalche; Ciunova-shuleska, Anita; Palamidovska-Sterjadovska, Nikolina (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2023)
The sharing economy is a business model that has revolutionized the way individuals travel, work, and engage with each other (Akhmedova et al., 2021). The rise of digital technologies has led to changes in how sharing is performed, making it simpler and more efficient (Teodorović and Orco, 2008). The present study focuses on ridesharing facilitated by Facebook rather than specialized commercial peer-to-peer (P2P) platforms. This form of ridesharing is a type of community-based sharing economy with a high level of contribution to a more sustainable economy but still has not received the deserved scientific attention (de Rivera et al., 2017; Wai Lai and Ying Ho, 2022). Facebook groups have emerged as viable platforms for peer-to-peer ridesharing (Santa and Ciunova-Shuleska, 2019), where drivers and passengers are using informal Facebook groups to pre-arrange and self-organize the riding while sharing the costs with no intention for financial gain (Eskelinen and Venäläinen, 2021). However, it is not only the economic exchange transaction that matters in this form of sharing but also the social benefit, which has its role in the subjective cost-benefit analysis and comparison of alternatives that individuals do when making decisions (Kim et al., 2015). The Social Exchange Theory can be used to comprehend how the interactions between people lead to the development of relationships, which people may choose to maintain or end depending on the advantages (costs and rewards) associated with the relationship (Boateng et al., 2019). This theory resonates with the specifics of the sharing economy concept which is also embedded in interpersonal exchanges (Kim et al., 2015; Yan et al., 2016). Through the Social Exchange Theory (SET) lens, the present study focuses on identifying the main benefits of using Facebook ridesharing and the main costs (risk/uncertainties) of its use. Based on this theory, we expect that users’ actual ride-sharing participation is driven by economic and social benefits (Hamari et al., 2016; Boateng et al., 2019). On the other hand, the cost of participating in ridesharing is the perceived risk and uncertainties in the arrangement and performing processes (Kim et al., 2015). By researching users’ behavior and underlying motivations, a deeper understanding of the sharing economy concept will be provided, and the strategies to encourage users’ interest. Furthermore, this study seeks to fill the research gap on the drivers of users' sharing behavior that has arisen in addition to the rising research focus on the sharing economy (Davlembayeva et al., 2020). Although previous research studies have focused on ridesharing via dedicated ridesharing platforms (Kooti et al., 2017; Wallsten, 2015), our study focuses on ridesharing via social media i.e., Facebook. Moreover, although previous research studies focused on analyzing users’ motivations to use ridesharing platforms (Amirkiaee and Evangelopoulos, 2018; Furuhata et al., 2017; Zhu, So, and Hudson, 2017) along with perceived risks (Wang, Wang, and Wang, 2019; Chean et al., 2022), it is still unclear what benefits, value and risks users perceive in sharing time and space with strangers using social media self-organizing ridesharing groups such as Facebook. This is even more important given that Facebook ridesharing groups do not have an online rating system that allows customers to rate drivers after the ride and to rely on drivers’ ratings before making the decision to share a ride (Aw, Basha, Ng, and Sambasivan, 2019; Anderson, 2016). So, this study will be the first study to analyze the motivations and risks of using ridesharing via social media self-organized ridesharing groups providing valuable insights into the perceptions and behavior of the participants in ridesharing groups on Facebook. The present research is based on a qualitative study applying focus groups as a data collection method. Focus groups are deemed suitable for this research as they provide exploration and generation of in-depth insights, opinions, and experiences of participants on the researched topic (Nyumba et al., 2018). The interactive nature of focus groups also facilitates group dynamics and the sharing of diverse perspectives. A convenience sample of 21 users of Facebook ridesharing groups was used, divided into three focus group sessions. The focus group sessions were conducted online and each lasted approximately 100 minutes, ranging from 88 to 112 minutes. The identified Facebook groups are dedicated to inter-city ridesharing in North Macedonia where more than ten public Facebook groups successfully assist in the organization of ridesharing in North Macedonia (Santa and Ciunova-Shuleska, 2019). The discussions were led by experienced moderators following a semi-structured list of questions/discussion topics, guiding the conversation and eliciting participants' thoughts, opinions, and experiences related to the research topic. The video recordings from each session were transcribed verbatim to maintain accuracy. Transcripts, along with any field notes taken during the sessions, were then subjected to a systematic coding process. The obtained qualitative data will be analyzed by applying a reflexive thematic analysis approach to provide deeper insights into the researched topics through interpretation (Braun and Clarke, 2021). The six-step process for reflexive thematic analyses is applied: 1) familiarity with the data, 2) generating initial codes, 3) constructing themes, 4) revising themes, 5) defining themes, and 6) reporting (Braun and Clarke, 2019). Based on the initial exploration of the data, we strive to identify the crucial functional and economic benefits of using community-based P2P ridesharing (e.g., convenience, lower price, etc.) as well as some social benefits (e.g., enjoyment, social belonging, social interactions). On the other side of the cost-benefit matrix, we expect users to report some concerns and potential costs, such as uncertainty regarding the arranged price, safety, reliability, emotional labor, etc. By identifying the economic and social aspects of the ridesharing exchange, this study will provide insights into the underlying reasons for users’ contribution to this form of sharing economy, thus obtaining a deeper understanding of the usage patterns.
Keywords: Facebook; ridesharing; Sharing economy; social exchange theory